Considering the ontological premises for tools in artists’ education - on poiesis and composition - Monni, Kirsi (My University, 2015)
Artikkeli käsittelee ‘työkalujen’ ongelmallisuutta taiteilijan koulutuksessa, erityisesti MA tason koreografian opetuksessa. Aihe on osoittautunut oleellisen tärkeäksi moninaisten ja heterogeenisten esteettisten tavoitteiden nykyajassa, sillä jokainen työkalu, kuten se konventionaalisesti ymmärretään, on käyttövalmis jo aiemmin varmistetun päämäärän ja metodin mukaan, ja siten se on jo osittain ratkaissut yksittäisen ja erityisen taiteellisen kysymyksen taiteilijan ja maailman välillä. Kysymys ‘työkaluista’ taiteellisessa prosessissa näyttäytyy minulle laajempana poetiikan (tekniikoiden, menetelmien, tiedon) kysymyksensä sekä poiesiksen ja taideteoksen ontologiaan liittyvänä kysymyksensä. Poetiikan teemaa käsiteltiin laajasti kuuden eurooppalaisen esittävän taiteen MA ohjelman Erasmus Intensive -projektissa vuosina 2011-2013. Tämä artikkeli raportoi joitain aspekteja tuosta keskustelusta ja kehittelee edelleen koreografian opetuksessa perinteisesti keskeisen komposition käsitteen analyysia. Voidakseni käsitellä poetiikan, työkalujen ja taideteoksen kompleksista suhdetta, pohdin ensin teoksen luomisen kysymystä poiesis käsitteen avulla ja sen jälkeen komposition ontologiaa erityisesti Martin Heideggerin logos käsitteen avulla. Esitän ajatuksen kompositiosta ‘yhteenkuuluvuus suhteisuudessa’ -tapahtumana ja että tällaista näkymää vasten komposition käsite voisi palvella taiteilijan, erityisesti koreografin, koulutuksessa sekä rakenteellisena reflektiona että syvällisenä taiteellisena tutkimuskysymyksenä.

This article considers the ontological premises for tools in artists’ education, specifically in choreography studies at the master-of-arts level. The topic has proven to be crucial in planning and executing a curriculum of study in the contemporary age of pluralistic aesthetic intentions as any tool, as habitually understood, is ready-to-use according to its disclosed purpose and thus has, in a way, already solved some aspects of the singular research question posed between the artist and the prevailing world. The topic of tools turns out to be a wider question of contemporary poetics (techniques, methods, knowledge) and of ontological considerations of the nature of poiesis and artwork. The topic of contemporary poetics was extensively discussed in a 2011-2013 Erasmus Intensive project, which was an educational collaboration among six European master’s programmes in dance and physically based performance in which the writer took part. This article reports some aspects of that discussion and elaborates on a traditionally widely used concept in choreography education—namely, composition. The article tackles the complex issue of poetics and tools by, firstly, discussing poiesis and the causes to which artwork is indebted and, secondly, by searching in some ontological premises for the notion of composition. The article presents a view of composition derived from Martin Heidegger’s elaborations of logos: logos is letting something been seen it its togetherness with something – letting it been seen as something. (Heidegger 1962, 56). Following this notion, I propose a view to composition as a certain togetherness in relatedness in which case the concept of composition might serve both as reflective knowledge of construction and as a deep research question in artists’ creative processes.
Keywords: poiesis; kompositio; yhteenkuuluvuus suhteisuudessa; Choreography.; Pedagogy.; Philosophy.; koreografia; opetus; menetelmät; taiteellinen työ; käsitteet; filosofia; koreografi; undervisning; metoder; konstnärligt arbete; begrepp; filosofi